Presentation of land‐use and traffic efficiency assessment - Behbahani, Hamid; Haghighi, Farshidreza (Journal of Environmental Engineering and Landscape Management, 2009)
Extensive research has shown that land use and transportation features are linked by a complex, yet identifiable, set of relationships, hence, in order to interpret this link and relationship, there are just a few investigations and models, especially in IRAN. Nowadays, Transportation Plans rarely acknowledge any feedback effects from transportation improvements on land use, and thereby ignore these effects in plan evaluation. This omission has the potential consequence of exaggerating mobility and environmental benefits of transportation projects and undervaluing the potential benefits of land use or transportation policies. This paper uses the main concepts of transportation efficiency of metropolitan transportation systems. It offers a neural model to measure and assess land use and transportation system efficiency. Besides the fact that many different factors work simultaneously, shaping our land use and its transportation efficiency, such as agricultural features, socioeconomic parameters, environmental parameters and so on, but in order to evaluate land use‐transportation efficiency, it is useful to consider just transportation infrastructure parameters. As long as through a region, land use conditions (especially transportation facility efficiencies) results in different travel behaviors, the region were divided into zones and are defined by individual or combinations of land use and transportation variables, such as network connectivity, pedestrian environment, density of activities, and other transportation infrastructure attributes. This neural‐based model uses GIS‐based data for each parcel of land use to evaluate its transportation efficiencies and result in percent of SOV (Self Occupancy Vehicle) trips through the region. SOV trip rates serve as a tool currently used for the evaluation of any land use and transportation efficiency through the region. The main concept of such an evaluation index is based on the fact that in a region, fulfilling the transportation accessibility needs will result in less use of SOV trips and vice versa. The model was calibrated and validated in neural network based on Tehran city’s GIS data and evaluated. In order to increase the accuracy of the results, the AHP Model was applied to operationlize various effects of input parameters into the neural model. The aim of this study was to increase acknowledgement of any feedback effects of transportation improvements on land use and providing such a tool for Transportation departments at state, federal and local levels. This model is a powerful tool to guide decision‐makers about whether to build new transportation facilities or maintain or improve the existing ones, evaluation of the land‐use efficiency and also comparing regions by some transportation facilities. Žemėnaudos ir transporto efektyvumo vertinimas Santrauka. Išsamūs tyrimai parodė, kad žemėnaudą ir transportavimo ypatumus sieja visuma identifikuojamų sąsajų, vis dėlto, siekiant paaiškinti tas sąsajas ir jų santykį, bent Irane, yra mažai tyrimų ir modelių. Nūdienos transporto planuose retai kada atsižvelgiama į transporto patobulinimą, įtaką žemėnaudai. Perdėtai teigiama transporto projektų nauda mobilumui ir aplinkai, nepakankamai įvertinant galimą žemėnaudos arba transporto politikos naudą. Straipsnyje remiamasi pagrindinėmis transporto efektyvumo didmiesčio transportavimo sistemoje sąvokomis. Siūlomas modelis išmatavus įvertinti žemėnaudą ir transportavimo sistemos efektyvumą. Kad būtų galima įvertinti transportavimo kiekviename žemėnaudos sklype efektyvumą ir nustatyti procentais privačių transporto priemonių reisus regione, naudojamasi GIS duomenimis. Pagal privačių transporto priemonių reisų dažnį pastaruoju metu vertinama žemėnauda ir transportavimo efektyvumas regione. Šio vertinimo esmė yra tai, kad regione, kuriame tenkinami transportavimo prieinamumo poreikiai, mažiau naudojama privačių transporto priemonių, ir atvirkščiai. Modelis buvo kalibruotas ir patvirtintas remiantis Teherano miesto GIS duomenimis ir įvertinimais. Siekiant padidinti rezultatų tikslumą AHP modelis buvo pritaikytas modeliuojant įvairią įvesties parametrų įtaką. Šio tyrimo tikslas – išryškinti transportavimo gerinimo žemės naudojimo atžvilgiu svarbą pristatant metodą valstybės, federalinės ir vietinės valdžios transporto departamentams. Šis modelis yra efektyvi priemonė, padedanti sprendimų priėmėjams nuspręsti, ar statyti naujas transportavimo infrastruktūras, ar atnaujinti, pagerinti esamas, jis paremtas žemės naudojimo efektyvumo įvertinimu ir leidžia palyginti regionus pagal kai kuriuos transportavimo ypatumus. Reikšminiai žodžiai: eismo vertinimas, žemėnauda, prieinamas, transportavimo efektyvumas, nervų sistemos tinklas. Оценка эффективности землепользования и систем транспортирования Резюме. Исследования показали, что землепользование и особенности транспортирования тесно взаимосвязаны. Для объяснения этой взаимосвязи в Иране существует несколько моделей. В настоящее время транспортные парки редко учитывают возможное, более совершенное применение земельных территорий. Это преувеличивает значение транспортных проектов для мобильности и окружающей среды и недостаточно учитывает возможную пользу от землепользования и транспортной политики. В статье основывались на концепциях эффективности транспортных систем больших городов. Предложена модель для оценки эффективности землепользования и систем транспортирования. Несмотря на то, что эффективность землепользования и транспортирования формируется на основании нескольких различных факторов (особенностей сельского хозяйства, социально-экономических, природоохранных параметров и др.), для оценки эффективности землепользования и транспортирования целесообразно оценивать лишь параметры транспортной инфраструктуры. Условия землепользования в масштабе региона обуславливают разное поведение при передвижении. Регион был поделен на зоны и охарактеризован индивидуальными и общими переменными, а именно: густотой сети, условиями для пешеходов, частотой транспортной инфраструктуры и другими чертами. Эта модель, основанная на структуре нервной системы, для каждого участка земли применяет данные ГИС для того, чтобы оценить эффективность транспортной системы и в процентном отношении эффективность рейсов транспортных средств в регионе. Частота самоходных транспортных средств в последнее время является средством оценки эффективности землепользования для транспортных нужд в регионе. Суть такой оценки заключается в том, что в регионе, в котором удовлетворяются потребности в возможностях транспортирования, используется меньше самоходных транспортных средств и наоборот. Модель была калибрована и утверждена на основании данных ГИС города Тегерана и соответствующих оценок. Целью исследования было выявить возможности улучшения транспортных условий с учетом землепользования и представить метод государственным, федеральным транспортным департаментам и местным властям. Модель может служить эффективным средством при принятии решения о том, создавать новые транспортные инфраструктуры или совершенствовать имеющиеся на основании оценки эффективности землепользования и сравнения регионов по особенностям транспортирования. Ключевые слова: оценка движения, землепользование, доступность, эффективность транспортирования, сеть нервной системы. First Published Online: 14 Oct 2010